Banking on Foreigners : The Behavior of International Bank Lending to Latin America, 1985–2000 - Martinez Peria, Maria Soledad (World Bank, Washington, DC, 2014)
Rising international bank financing to developing countries has fueled a debate on the behavior of these claims. The authors analyze claims from seven home (lender) countries on ten host (borrower) countries in Latin America. They find that banks transmit shocks from their home countries and changes in their claims on other countries spill over to individual hosts. However, lending has become less "indiscriminate" and more responsive to host conditions over time. Responsiveness to the latter becomes less "pro-cyclical" as exposure increases. Finally, foreign bank lending reacts more to positive than to negative host shocks and is not significantly curtailed during crises.